МОДИФИЦИРОВАНИЕ КОЛЛАГЕНА И ЖЕЛАТИНА ПОД ДЕЙСТВИЕМ МИКРОВОЛНОВОГО ПОЛЯ (World Science, 2020)
The microwave field influence on the physicochemical properties of collagen and gelatin was studied. It is shown that when microwave field acts on the studied protein samples, a change in the molecules structure formation occurs. It was experimentally established that microwave exposure leads to the structural modification of collagen and gelatin molecules. This modification is accompanied by a change in the physicochemical properties of the studied biopolymers. It is shown that microwave field exposure leads to a decrease in the viscosity of collagen and gelatin solutions. A decrease in viscosity indicates that there’s a structural or transient processes occurring in protein molecules.The kinetics of swelling with time for collagen and gelatin samples was studied. It is shown that the use of a microwave field leads to a decrease in the rate constant of swelling. The swelling degree of the studied samples decreases on average by 60%. It is shown that isoelectric points of the proteins are shifted (pI from 5 to 6 for collagen and up to 5.5 for gelatin).